'Don't let your child become a NEET!' The strategic foundations of a Japanese youth scare - Toivonen, T (Routledge, 2011)
This article contributes to the growing body of literature on Japanese youth problems by tracing and unpacking a recent moral panic surrounding young people identified as ‘NEETs’ for being ‘not in education, employment or training’. While sharing many key features with other mainstream youth problems in Japan, the case of ‘NEETs’ illuminates particularly well the strategic interplay of social labels and more technical policy categories. To this end, a clear distinction is made between the social category nīto and the policy target group ‘NEET’. Close attention is paid to how these were re-defined in the Japanese context, including how the latter came apply to a remarkably expansive age group (15–34-year-olds). Most importantly however, the account highlights the central actors and interrogates their respective interests, providing strong support for the argument that the ‘NEET problem’ amounted ultimately to a strategic campaign designed to clear the way for new youth policies. The findings explicated will contribute to our understanding of high-profile youth scares as well as other social problems in Japan that operate through the media but are intimately linked to policy-making.